2011
DOI: 10.1007/s10964-011-9684-0
|View full text |Cite
|
Sign up to set email alerts
|

Early Adolescent Peer Ecologies in Rural Communities: Bullying in Schools That Do and Do not Have a Transition During the Middle Grades

Abstract: The transition to middle school is considered to be a heightened period for involvement in bullying because the lack of a defined dominance hierarchy is thought to promote jockeying for social positions among students. Accordingly, this study examined bullying in peer ecologies at the beginning of the middle grade years in rural schools that did and did not have a transition to middle school. Thirty-six schools (20 with transitions, 16 without transitions) participated in this research with a sample of 1,800 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 35 publications
2
66
0
Order By: Relevance
“…Along similar lines, Farmer, Hamm, Leung, Lambert, and Gravelle () showed that the risk of bullying involvement may be elevated where there is no transition from one school to another as children move from elementary to middle school grades: Compared with students in schools with a transition, students in schools without one were more likely to bully and be bullied and perceived the peer ecology as less protective against bullying, after entering the middle school grades. The authors suggested that breaking up existing dominance structures in adolescent peer groups might buffer against bullying.…”
Section: Demographic and Structural Characteristicsmentioning
confidence: 89%
See 1 more Smart Citation
“…Along similar lines, Farmer, Hamm, Leung, Lambert, and Gravelle () showed that the risk of bullying involvement may be elevated where there is no transition from one school to another as children move from elementary to middle school grades: Compared with students in schools with a transition, students in schools without one were more likely to bully and be bullied and perceived the peer ecology as less protective against bullying, after entering the middle school grades. The authors suggested that breaking up existing dominance structures in adolescent peer groups might buffer against bullying.…”
Section: Demographic and Structural Characteristicsmentioning
confidence: 89%
“…In fact, some studies suggest the opposite (Dulmus, Theriot, Sowers, & Blackburn, ; Klein & Cornell, ). It has been suggested that in rural schools—many of which are small and do not have a transition, which may result in a rather static social community and consolidation of social reputations—bullying may be a byproduct of students' efforts to maintain the existing dominance structure (Farmer et al, ).…”
Section: Demographic and Structural Characteristicsmentioning
confidence: 99%
“…Students in schools with formal transition programs are less frequently bullied in the move from 5th to 6th grade as the social dynamics are less supportive of bullying than schools without transition programs. The risk of involvement in bullying is higher in schools that do not have a transition to middle school, which questions the conventional view of K-8 or K-12 rural schools as peaceful and supportive peer communities (Farmer, Hamm, Leung, Lambert & Gravelle, 2011).…”
Section: Student Belonging and Well-beingmentioning
confidence: 90%
“…By being attuned to the social dynamics of their students, teachers are in a better position to structure their classrooms in ways that reduce conflict among youth, promote engagement of all students, and create opportunities for victimized students to gain status among their peers (Farmer et al, 2011; Rodkin & Hodges, 2003). Attunement to victimization may help teachers anticipate and prevent or intervene in bullying situations; in turn, by modeling effective strategies for intervening in bullying, students may feel more confident that they themselves can effectively come to the aid of their victimized peers.…”
mentioning
confidence: 99%